Piezoelectric vibration control through fuzzy logic for direct current converter - Mohamad Arinal, Abdul Halim; Mohd Nadhir, A. Wahab; Fathinul Syahir, Ahmad Sa'ad; Muhammad Juhairi Aziz, Safar; Hasimah, Ali (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher’s homepage at http://ieeexplore.ieee.org/